Derivative use, fund flows and investment manager performance - Frino, Alex; Lepone, Andrew; Wong, Brad (Journal of Banking & Finance, 2009)
Prior literature which examines the use of derivatives by investment managers does not discern between different types of derivative trading strategies. This study is the first to examine and gather data on a particular type of derivative trading strategy undertaken by investment managers. We examine the extent to which equity fund managers use index futures to manage fund flows and the effect this has on their alpha and market timing measures of performance. Our results show that funds that do not use derivatives exhibit lower returns and negative market timing skills when they experience fund flow. The performance of funds that use derivatives, however, is independent of investor’s liquidity demands. In fact, the unconditional performance of the average user fund is statistically equivalent to the performance of the average non-user fund conditional on zero fund flow. Our results provide evidence that derivatives can be beneficial for mutual fund holders under certain conditions.